Treatment of Post-traumatic Bone Defects with Infection in Long Bones - Hari Om Aggarwal; Sreen SK; Singh M; Banga RK; Bansal H (GMC Patiala Journal of Research and Medical Education, 2018)
Masquelet technique, which is the use of a temporary cement spacer followed by staged bone grafting, is a recent treatment strategy to manage an infected nonunion with bone defect. This paper describes a series of 20 patients treated with this technique of staged bone grafting following placement of an antibiotic spacer to successfully manage infection as well as bone defects in long bones. The injured limbs were stabilized and aligned at the time of initial spacer placement. In our series, osseous consolidation was successfully achieved in all cases. This technique gives promising result in the management of post-traumatic bone defects associated with infection.